IL-1 Signaling Is Critically Required in Stromal Cells in Kawasaki Disease Vasculitis Mouse Model: Role of Both IL-1α and IL-1β. Issue 12 (December 2015) - Lee, Youngho; Wakita, Daiko; Dagvadorj, Jargalsaikhan; Shimada, Kenichi; Chen, Shuang; Huang, Ganghua; Lehman, Thomas J.A.; Fishbein, Michael C.; Hoffman, Hal M.; Crother, Timothy R.; Arditi, Moshe
Abstract : Objective—: Kawasaki disease (KD) is the most common cause of acute vasculitis and acquired cardiac disease among US children. We have previously shown that both TLR2/MyD88 and interleukin (IL)-1β signaling are required for the Lactobacillus casei cell wall extract–induced KD vasculitis mouse model. The objectives of this study were to investigate the cellular origins of IL-1 production, the role of CD11c + dendritic cells and macrophages, and the relative contribution of hematopoietic and stromal cells for IL-1 responsive cells, as well the MyD88 signaling, in Lactobacillus casei cell wall extract–induced KD mouse model of vasculitis. Approach and Results—: Using mouse knockout models and antibody depletion, we found that both IL-1α and IL-1β were required for Lactobacillus casei cell wall extract–induced KD. Both dendritic cells and macrophages were necessary, and we found that MyD88 signaling was required in both hematopoietic and stromal cells. However, IL-1 response and signaling were critically required in nonendothelial stromal cells, but not in hematopoietic cells. Conclusions—: Our results suggest that IL-1α and IL-1β, as well as CD11c + dendritic cells and macrophages, are essential for the development of KD vasculitis and coronary arteritis in this mouse model. Bone marrow chimera experiments suggest that MyD88 signaling is important in both hematopoietic and stromal cells, whereas IL-1 signaling and response are required only in stromal cells, but not in endothelial cells. Determining the role of IL-1α and IL-1β and of specific cell types in the KD vasculitis mouse model may have important implications for the design of more targeted therapies and understanding of the molecular mechanisms of KD immunopathologies. Abstract : Supplemental Digital Content is available in the text.